Evaluasi Program Pemberdayaan Bintara Pembina Desa Komando Distrik Militer 0503/Jakarta Barat - Harangan Sitorus (Universitas Pertahanan Republik Indonesia (UNHAN RI), 2018)
Abstract – This study aimed to evaluate the empowerment program of (NCO) of Village Builder in The District Military Command 0503 / West Jakarta. The research method was descriptive qualitative, using DEM model (Discrepancy Evaluation Model). Data collection procedures through primary data and secondary data obtained through observation, interviews, documentation and Focus Group Discussion (FGD). Furthermore, all data is analyzed to obtain the results. The Validation of the data was carried out through triangulation. The results showed that the empowerment program (NCO) Village Builder The District Military Command 0503 / West Jakarta review of aspects of drafting stage of program design (definition), the stage of determination of completeness (installation), the stage of implementation of the empowerment program (NCO) Village Builder (process), the stage of the measurement results (produck) and comparison phase, overall shows less effective results. To increase the effectiveness of development programs further provided recommendations according the result of research analysis.Keywords: program evaluation, empowerment, Non-Commissioned Officers (NCO) Village Builder Abstrak – Penelitian ini bertujuan untuk mengevaluasi program pemberdayaan Bintara Pembina Desa Komando Distrik Militer 0503/Jakarta Barat. Metode penelitian ini adalah deskriptif, kualitatif, dengan menggunakan model DEM (Discrepancy Evaluation Model). Prosedur pengumpulan data melalui data primer dan data sekunder yang didapatkan melalui observasi, wawancara, dokumentasi dan Focus Group Discussion ( FGD). Selanjutnya seluruh data dilanalisis untuk mendapatkan hasil penelitian. Validasi data dilakukan dengan triangulasi. Hasil penelitian menunjukkan bahwa program pemberdayaan Bintara Pembina Desa Kodim 0503/Jakarta Barat ditinjau dari aspek tahap penyusunan desain program (definition), tahap penetapan kelengkapan ( installation ), tahap pelaksanaan program pemberdayaan Babinsa (process), tahap pengukuran hasil (produck) dan tahap pembandingan (comparison) secara keseluruhan menunjukkan hasil yang kurang efektif. Untuk peningkatan efektifitas program pemberdayaan selanjutnya diberikan rekomendasi sesuai hasil analisis penelitian.Kata kunci: Evaluasi program, Pemberdayaan, Bintara Pembina Desa